Investigation into the outlying swirl instability in the hydro-turbine draft tube under part-load operation. (February 2021) - Muhirwa, Alexis; Cai, Wei-Hua; Li, Feng-Chen; Su, Wen-Tao; Binama, Maxime; Li, Biao; Li, Xiao-Bin
The swirling trajectory of the draft tube flow improves the pressure recovery. Resultant flow instabilities are still problematic for an optimized hydropower generation. Engineering solutions are getting increasing importance. However; the depth of wall-mounted countermeasures is a challenging parameter. Performance assessment of countermeasures would rate dampened pressure pulsations in terms of their sources so as to place them at a proper location. A method for evaluating the instability in the outlying domain of the draft tube cone is herein suggested. Two part-load operating points with opposite polarity in pressure pulsations have been investigated. The numerical approach of Shear Stress Transport has been used, and experimental agreement of measurements for the pressure spectra is verified at the wall. Inlet flow conditions and the growth of the core instability are described. The outlying domain of the draft tube has been found to be composed of three distinct zones of influence: the shortest upper cone with upstream travelling influences, the longest middle cone with core excitation, and the lowermost cone dominated by the backward elbow influence. The wall response lies within a definite high-frequency range proper to the operating point. During admission, the frequency range becomes even wider due to high kinetic energy and the highest pressure amplitude of the draft tube is developed by the impact of blade passing frequency. The excitation from the vortex rope precession in the outlying domain strongly depends on the operating condition. Thus, further works should extend this study over a wider operation range, and mount pressure sensors on countermeasures in order to identify their own instability contribution.